Bruxism's Implications on Fixed Orthodontic Retainer Adhesion - Anca Labuneț; Adriana Objelean; Oana Almășan; Andreea Kui; Smaranda Buduru; Sorina Sava (MDPI AG, 2022)
Background: Fixed retainers assist in maintaining the outcomes of orthodontic treatment. Fixed retention may be affected by bruxism. Objective: Evaluate two adhesives (an ormocer and a flowable composite) used for fixed orthodontic retention in simulated bruxism settings, compared to regular mastication, using a dual axis chewing simulator. Methods: Eighty human teeth were used. Periodontal tissues were simulated and exposed to 120,000 mechanical cycles, corresponding to 6 months of clinical service. Each set of two teeth was supplied with a pre-shaped, fixed, multi-braided, stainless steel wire retainer, in 1.5 cm portions, to establish passive contact with the lingual surface of the teeth. The Adhesive Remnant Index (ARI) was used to evaluate the shear bond strength. A stereomicroscope was used to assess the micro-infiltration. Results: There was no significant difference in the mean value of micro-infiltration between adhesives in the mastication group but in the bruxism group. During testing, one composite sample (ARI score 1) was broken in the mastication group, while three ormocer samples (ARI score 2) and one composite sample (ARI score 1) were broken in the bruxism group. Conclusions: The mean value for micro-infiltration in composite (0.31) was more than double that in ormocer (0.13).